KEBERADAAN MULTI SERIKAT PEKERJA PADA SUATU PERUSAHAAN - Frini Karina Andini (Universitas Riau, 2016)
The presence of the Multi Unions at the Company. This research uses descriptive qualitative research methods. The informants are PT. Indah Kiat Pulp & Paper Tbk and unions. Sampling using snawball sampling. Data collection through in-depth interviews, observation and documents. Data analysis techniques drawn from data presentation, data reduction, verification and conclusion. These results indicate that the presence of multiple unions provide its own dynamics for the company. The Company obtained a variety of different aspirations and demands of the four unions. However, from the union it does not show the split between them, even though they can unite aspirations through the stages quite long.